PERILAKU DAN SIKAP MANAJER PRODUKSI USAHA KECIL DAN MENENGAH: KAJIAN TEORI PERILAKU - Setyabudi Indartono (JURNAL ILMU MANAJEMEN, 2018)
This study is aimed to explore various models of behaviors and attitude of production manager of small medium enterprises. The theoretical perspectives are used to evaluate their behavior and attitude at work. The various points of view is believed to generate different angles of behavioral and attitudinal criteria. Hence the characteristic of job and basic conditions of the business and managers to be considered on the analysis of this study. The antecedents and outcomes of their behavior and attitudes conclude on this study to represent the general behaviors and attitude of production manager for small medium enterprises. Limitations and future research are discussed